Peningkatan Keterampilan Menyusun Teks Deskripsi Melalui Pembelajaran dengan Media Mind Map pada Siswa Kelas VII E SMP 2 Kumai - Fauziah Fauziah (Anterior Jurnal, 2022)
This CAR is a classroom action research that examines the improvement of the ability to write descriptive texts in class VII E SMP 2 Kumai students. The purpose of this study was to determine the improvement of compiling descriptive text through learning using appropriate mind map media for Indonesian descriptive text material based on the 2013 curriculum in Keels VII E of SMP 2 Kumai students. The classroom action research process is carried out in two cycles, each of which includes four main stages, namely planning, action, observation, and reflection. The instruments used are test and non-test. The test instrument is to get a score for the ability to write a descriptive text. The non-test instrument used by the researcher was a journal, an observation guide to obtaining data about students' abilities in writing descriptive texts. The results showed that the use of mind map media can improve students' writing descriptive text skills. The results of the analysis above show that the action hypothesis in this study is in accordance with the expectation that the use of mind map media can improve the ability to write a descriptive text. The results of this study can provide benefits for schools, teachers in the field of study, and students, especially those related to improving the ability to write descriptive texts.